Proposed Improvements in Shrimp Business Productivity - Irwan Efendi; Meri Andriani; Heri Irawan (JURUTERA - Jurnal Umum Teknik Terapan, 2024)
Makmur Jaya is a vaname shrimp farming business, located in Kebun Kelapa Village, Secanggang District, Stabat. The problem faced by SMEs. Makmur Jaya is that poor input utilization causes productivity to decline. The research objective is to identify productivity and productivity improvement strategies at SMEs. Makmur Jaya. The method used in this research is the American Productivity Center (APC) method. The results of the study, the largest increase in the productivity index in period 4 by 1% while the largest decrease in the productivity index in period 2 by -46.74%, the highest increase in the profitability index in period 3 by 1% while the highest decrease in profitability index in period 2 by -55.06%, and the largest price improvement index occurred in capital period 2 by 1.62, while the smallest price improvement index occurred in material period 2 by 0.79. The study concludes that the decline in productivity occurred in period 2 by 46.74%, so it is necessary to increase productivity. Strategy to increase productivity in SMEs. Makmur Jaya is minimizing the use of inputs to produce large outputs. Based on the results of the calculation, the input can be reduced by 36.49% (RP. 107,969,896) and the output can be increased by 56.53% (RP. 107,296,767) so that the total productivity increases by 0.94% from the initial total productivity.